Inclusão de alunos cegos nas classes regulares e o processo de ensino e aprendizagem de matemática - Splett, Elisa Seer (2015)
In the context of social inclusion, there are many and constant challenges faced by teachers in classrooms. Particularly, regarding the process of teaching and learning mathematics, the difficulties are even bigger, mostly when dealing with blind students. The main objective of this research was to know and analyze such difficulties, as well as understand which methodologies are used by Mathematics teachers that work with blind students in their classrooms. For this, it was decided to develop a case study in a public school in Santa Maria, Rio Grande do Sul, Brazil with an eighth grade class in which a blind student studies. In addition to observing classes, some other research instruments were used, such as a questionnaire with teachers and an interview with the school special educator. Theoretical foundation shows a historical review about the social inclusion policies and a little about the assistive technologies used by blind students to facilitate the process of studying and learning mathematics by them. Then, the adapted teaching materials which have been made to develop a didactic sequence in a class with blind students are presented. This activity was indented to help teachers in classrooms, showing that it is possible to develop methodologies that allow an integrated work with all the class students, which somehow interferes positively in the process of teaching and learning mathematics. In analyzing the data it used Bardin 's content analysis where the categories found and listed during the research were described . During the research, we sought to understand how is going to include in a regular education class, having as one of the research subjects the mathematics teacher who normally does not have special training to work in the context of inclusion. We also seek to show that mathematics when contemplating the use of concrete manipulatives in the classroom , makes this more enjoyable discipline for the student and gives opportunity greater integration among all students, including students with disabilities .